Toward the existence and uniqueness of solutions for fractional integro-differential equations under uncertainty - Hosseini, Ali Ahmadian; Ismail, Fudziah; Senu, Norazak; Salahshour, Soheil; Suleiman, Mohamed (AIP Publishing, 2016)
The main contribution of the current paper is to obtain new results on the existence and uniqueness of the solution of fractional integro-differential equations under uncertainty with nonlocal conditions. For this purpose, we have used two basic tools, the contraction mapping principle and Krasnoselskii's fixed-point theorem. Indeed, we have considered the original problem involving fuzzy Caputo differentiability, together with fuzzy nonlinear condition.